Analysis of Professionalism and Personality Competencies of Physics Teacher Candidates Through Laboratory Assistance Program - Azis, Anggraeni Dawama; Syahfirra, Gaurin Rani Masyitha; Nisa, Maulidia Khoirun; Anjani, Melly Yuni; Parno, Parno (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
The role of teachers in the educational process requires adequate professional qualifications to carry out their duties and responsibilities effectively. Standards for academic qualifications and teacher competency are regulated nationally, with personality and professional competency being the most significant. Students as prospective teachers need to have these qualification standards. This study aims to examine the professionalism and personality competencies of prospective physics teachers through a laboratory assistance program. A qualitative approach with a collective case study design was used to analyze data from 8 physics education students participating in the program. The results show that this program helps physics education students develop professional competence through problem-solving processes during laboratory activities. Meanwhile, personality competence is formed through self-control awareness and the development of student character. Thus, the laboratory assistance program has proven to be effective in preparing physics education students with the necessary competencies to become quality teachers.